Pharmacokinetic non-interaction analysis in a fixed-dose formulation in combination of atorvastatin and ezetimibe - Patiño-Rodríguez, Omar; Torres-Roque, Irma; Martínez-Delgado, Maricela; Escobedo-Moratilla, Abraham; Pérez-Urizar, José (Frontiers in Pharmacology, 2014)
Recent clinical research has shown that atorvastatin in combination with cholesterol absorption inhibitor ezetimibe significantly reduces LDL-C level in patients with hypercholesterolemia, showing a superior lipid-lowering efficacy compared to statin alone. With no information currently available on the interaction between the two drugs, a pharmacokinetic study was conducted to investigate the influence of ezetimibe on atorvastatin and conversely when the two drugs were coadministered. The purpose of this study was to investigate the presence of differences in the pharmacokinetic profiles of capsules containing atorvastatin 80 mg, ezetimibe 10 mg or the combination of both 80/10 mg administered to healthy Mexican volunteers. This was a randomized, three-period, six-sequences crossover study. 36 eligible subjects aged between 20 to 50 years were included. Blood samples were collected up to 96 h after dosing, and pharmacokinetic parameters were obtained by non-compartmental analysis. Adverse events were evaluated based on subject interviews and physical examinations. Area under the concentration-time curve (AUC) and maximum plasma drug concentration (Cmax) were measured for each drug alone or together and tested for bioequivalence-based hypothesis. The estimation computed (90% confidence intervals) for AUC and Cmax, were 96.04% (85.88%–107.42%) and 97.04% (82.36%–114.35%), respectively for atorvastatin-ezetimibe combination versus atorvastatin alone, while 84.42% (77.19%–92.32%) and 95.60% (82.43%–110.88%), respectively, for atorvastatin-ezetimibe combination versus ezetimibe alone were estimated. These results suggest that atorvastatin and ezetimibe have no relevant pharmacokinetic drug-drug interaction.